Design and implementation of the hybrid system for encryption and hiding the text file in the Voice over Internet Protocols. (المجلة العراقية للعلوم الاحصائية, 2011)
The immense development in the communication network has opened new spheres that threaten the data security transferred via the communication networks. As a consequence the techniques of encryption and information hiding and merging them to increase the security of data sent. The paper presents suggestion and design for a system to send data secretly by merging encryption technique and information hiding using steganography technique and covert channels to hide the data. The secret data needed to be sent encoded by using Data Encryption Standard (DES) algorithm or by Triple Data Encryption Standard (TDES) algorithm. Then the encoded data were hidden in a form of colored image of BMP type using Least Significant Bit technique (LSB). The covert channels of Voice Over Internet Protocol used its type value based spatial channel and active behavior to send the stego-image or text file using )Session Initial Protocol(SIP) Session Description Protocol(SDP) Real-Time Transport Protocol (RTP), Real-Time Transport Control Protocol(RTCP)(. The results have been retrieved hidden information properly for all the protocols. The hiding in image was done by using one slide or three slides of image in one bit or two bits or three bits where the transfer taken place from one pixel to another either by using one key or two key or three key. It is concluded that the hiding in one bit given less error value but with longer execution time that is the value of MSE depends on the number of bits were changed and by using multiple keys to increase the secrecy with the guarantee of not losing the data. Visual C# and Matlab7.6 (R2008a)were used in the programming.